Theologically engaged anthropology - Lemons, J. Derrick; Lemons, J. Derrick (Oxford, United Kingdom : Oxford University Press, 2018)
"After years of discussion within the field of anthropology concerning how to properly engage with theology, a growing number of anthropologists now want to engage with theology as a counterpart in ethnographic dialogue. Theologically Engaged Anthropology focuses on the theological history of anthropology, illuminating deeply held theological assumptions that humans make about the nature of reality, and illustrating how these theological assumptions manifest themselves in society. This volume brings together leading anthropologists and theologians to consider what theology can contribute to cultural anthropology and ethnography. It provides anthropologists and theologians with a rationale and framework for using theology in anthropological research."--
Introduction: Theologically engaged anthropology / J. Derrick Lemons -- 1. New insights from an old dialogue partner / J. Derrick Lemons -- 2. Which theology for anthropology? Types of theology for anthropological engagement / Brian M. Howell -- 3. The dependence of sociocultural anthropology on theological anthropology / Timothy Larsen, Daniel J. King -- 4. Theology revealing the Hajibs of Anthropology / Khaled Furani -- 5. What can theology contribute to cultural anthropology? / Paul Kollman -- 6. Theology's contribution to anthropological understanding in T. M. Luhrmann's When God Talks Back / Timothy Jenkins -- 7. Narratives of significance: reflections on the engagement of anthropology and Christian theology / Alister E. McGrath -- 8. An anthropologist is listening: a reply to ethnographic theology / James S. Bielo -- 9. Anthropology, theology, and the problem of incommensurability / Jon Bialecki -- 10. Superstition and enlightenment: engagements between theology and anthropology / Nicholas Adams -- 11. Anthropology and theology: fugues of thought and action / Douglas J. Davies -- 12. Athens engaging Jerusalem / Michael A. Rynkiewich -- 13. World Christianity and the reorganization of disciplines: on the emerging dialogue between anthropology and theology / Joel Robbins -- 14. Latter-Day Saints and the problem of theology / Fenella Cannell -- 15. Theology on the ground / Naomi Haynes -- 16. Comparative theology: writing between worlds of meaning / Francis X. Clooney, SJ -- 17. Passionate coolness: exploring mood and character in ecclesial polity / Martyn Percy -- 18. The exclusive brethren "Doctrine of separation": an anthropology of theology / Joseph Webster -- 19. Divinity inhabits the social: ethnography in a phenomenological key / Don Seeman -- 20. Anthropological and theological responses to theologically engaged anthropology / Sarah Coakley, Joel Robbins
Includes bibliographical references (pages 377-384) and Index.
Keywords: Theological anthropology; Theological anthropology -- Christianity; Bible and anthropology; Theological anthropology -- Christianity; Theological anthropology; Bible and anthropology